Group Guidance Services Based on Problem-Solving with the Integration of Digital Media (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
This study aims to review and analyze previous research on the effectiveness of group guidance services based on problem-solving integrated with digital media. The study employed a Systematic Literature Review (SLR) method by analyzing 25 national and international scientific articles published between 2018 and 2024. The article search was conducted through Google Scholar, DOAJ, Sinta, and Scopus using the keywords “group guidance,” “problem-solving,” “digital media,” and “learning motivation.” The findings indicate that group guidance services based on problem-solving are effective in improving students’ problem-solving skills, emotional regulation, and learning motivation. The integration of digital media has been proven to enhance student engagement, service effectiveness, and learning adaptation in the digital era. This study recommends that guidance and counseling teachers as well as school counselors develop more innovative and interactive technology-based guidance service models